2023
DOI: 10.1093/infdis/jiad030
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Severe Acute Respiratory Syndrome Coronavirus 2 Vaccination and Infection on Neutralizing Antibodies: A Nation-wide Cross-sectional Analysis

Abstract: Background Neutralising antibodies (nAbs) play a critical role in the protection against severe COVID-19. In the era of vaccine boosters and repeated SARS-CoV-2 outbreaks, identifying individuals at risk represents a public health priority. Methods Relying on the Monaco COVID Public Health Programme, we evaluated nAbs from July 2021-June 2022 in 8,080 SARS-CoV-2 vaccinated and/or infected children and adults, at their inclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…This coincides with our previous study which showed that breakthrough infection after the two-dose CoronaVac vaccination induced a higher level of Ig anti-RBD than two-dose CoronaVac vaccination alone and the third dose vaccination with AZD1222 but comparable to those achieved by the third dose BNT162b2 booster [ 16 , 17 , 18 , 19 ]. A large cohort in Monaco also showed that hybrid immunity induces high levels of neutralizing antibody against SARS-CoV-2 [ 27 ]. Another study in Denmark which compared between fully BNT162b2 vaccinated individuals with and without previous SARS-CoV-2 infection also found that the proportion of individuals with high levels of total SARS-CoV-2 antibodies was significantly higher in those with prior infection (72.2%) than in infection-naïve individuals (35.4%), indicating robust humoral response induced by hybrid immunity [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This coincides with our previous study which showed that breakthrough infection after the two-dose CoronaVac vaccination induced a higher level of Ig anti-RBD than two-dose CoronaVac vaccination alone and the third dose vaccination with AZD1222 but comparable to those achieved by the third dose BNT162b2 booster [ 16 , 17 , 18 , 19 ]. A large cohort in Monaco also showed that hybrid immunity induces high levels of neutralizing antibody against SARS-CoV-2 [ 27 ]. Another study in Denmark which compared between fully BNT162b2 vaccinated individuals with and without previous SARS-CoV-2 infection also found that the proportion of individuals with high levels of total SARS-CoV-2 antibodies was significantly higher in those with prior infection (72.2%) than in infection-naïve individuals (35.4%), indicating robust humoral response induced by hybrid immunity [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…A third dose booster vaccination was necessary to boost the immune response and increase protection against symptomatic COVID-19 infections [ 9 , 13 , 14 , 15 ]. Recent studies that examine the dynamics of neutralizing antibody levels induced by two-dose and three-dose vaccination in infection-naïve individuals also showed that the durability of antibody improves after three-dose vaccination [ 27 ]. Besides, individuals reporting prior infection with SARS-CoV-2 exhibited significantly higher neutralizing titres compared to those without breakthrough infection [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2023 ). Indeed, S:S740L, the mutation with greater differences in the vaccination probability, arose again in 2022 connected with several Omicron sub-lineages and it is estimated that S:S704L increased the growth advantage of the baseline BA.2 lineage by a 35 per cent ( Althaus et al. 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…This observation was consistent across age groups. Most studies 35 – 40 found that individuals with hybrid immunity had the highest anti-spike IgG titres and neutralising responses followed by vaccinated and then infected individuals, but most of these studies focussed on adults. A study by Zaballa et al 7 , found that neutralising activity, especially for Omicron BA.1 and even more so for subsequent subvariants (Omicron BA.2, BA.2.12.1, BA.4/BA.5), was much lower in children and adolescents compared to our study despite the use of the same assay 41 .…”
Section: Discussionmentioning
confidence: 99%